Penerapan Fuzzy Inference System (FIS) Dengan Metode Mamdani Pada Sistem Prediksi Penjualan Laptop - Herwin Syah (JMAI (Jurnal Multimedia & Artificial Intelligence), 2019)
The high purchase of laptops makes the sellers or laptop shops increase their laptop stock. A store prior to marketing a product must plan and predict the results of sales or in other words, sales management must be properly analyzed so that the sales results obtained are also in line with expectations. The number of competitors in sales is a challenge that must be passed by all stores or product sellers. laptops also have different quality, specifications and capabilities that can affect sales to buyers. The seller must be careful in determining the brand laptops and specifications that are in great demand by consumers. This research is aimed at applying fuzzy logic with the mamdani method in concluding quickly to determine the brands and specifications of how we should sell to consumers who have good sales. The results of the application of mamdani's fuzzy logic method (FIS), that sales of laptops are seen from the value of the brand, price, specifications and warranty period can be done. And can determine the laptop with categories such as what are selling well enough.